2021
DOI: 10.1161/hypertensionaha.120.16774
|View full text |Cite
|
Sign up to set email alerts
|

BEX1 Is Differentially Expressed in Aldosterone-Producing Adenomas and Protects Human Adrenocortical Cells From Ferroptosis

Abstract: Aldosterone-producing adenomas (APAs) are a major cause of primary aldosteronism. Somatic mutations in ion channels and transporters drive the aldosterone overproduction in the majority of APAs with mutations in the KCNJ5 G protein-coupled potassium channel predominating in most reported populations. Our objective was to gain insight into biological mechanisms of APA tumorigenesis by comparing transcriptomes of APAs of distinct sizes by mRNA sequencing analysis (9 APAs with adenoma diameter ≥30 mm versus 12 AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 49 publications
(89 reference statements)
1
20
0
Order By: Relevance
“…It has been reported that adrenocortical cells are sensitive to ferroptosis-triggering agents, such as RSL3, which can inhibit GPX4 activity [17,45]. Indeed, our data showed elevated GPX4 expression in APAs compared with adjacent zona glomerulosa.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…It has been reported that adrenocortical cells are sensitive to ferroptosis-triggering agents, such as RSL3, which can inhibit GPX4 activity [17,45]. Indeed, our data showed elevated GPX4 expression in APAs compared with adjacent zona glomerulosa.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, we demonstrated a functional link between lipid biology and ferroptosis. This is relevant because adrenocortical cells have previously been shown to be highly sensitive to cell death by ferroptosis due to the inhibition of glutathione biosynthesis (Figure 2A) [17,44,45]. Of note, the ferroptosis suppressor gene coding for glutamate-cysteine ligase catalytic subunit (GCLC) and the gene coding for stearoyl-CoA desaturase (SCD) are highly expressed in APAs compared with adjacent zona glomerulosa (Figure 2C).…”
Section: Transcriptome Defined Metabolic Reprogramming Towards Fatty Acid β-Oxidation and Glycolysis In Apasmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, both micro-APAs and APAs present higher BEX1 expression with CACNA1D, ATP1A1 or non-KCNJ5 mutations. This gene is involved in ferroptosis, and it is hypothesized that increasing APA size leads to reduction of the need for anti-ferroptotic mechanisms [ 25 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…To detect mechanisms of APA tumorigenesis, Yang et al. ( 73 ) compared APA transcriptomes of highly diverse sizes (9 macro APAs with adenoma diameter ≥30 mm versus 12 micro APAs ≤10 mm). Over-representation analysis of the transcriptome dataset from Yang et al.…”
Section: Transcriptomics Of Aldosterone-producing Adenomasmentioning
confidence: 99%